Assessment of the molten pool initial state during degradation of the reactor core with horizontal fuel assemblies arrangement - Filonov, Vladislav; Fedorov, Dmytro (Національний технічний університет "Харківський політехнічний інститут", 2024)
The paper examines the first approximation in the assessment of the corium initial state in the lower plenum during the in-vessel phase late stage of severe accident of a promising small modular reactor of the ESS-SMART project [1]. The features of the presented analysis are related to both the initial supercritical state of the coolant and the horizontal layout of the core in the form of a system of parallel fuel assem-blies with a seven-level coolant inlet system [2]. Existing industry computational system tools are limited in representing the original geo-metric configuration of the reactor flow path, and in particular the reactor core. Moreover, significant difficulties still arise taking into ac-count the pressure decreasing from a supercritical state to a two-phase state, which seriously limits the performance of estimates using the analytical tool only. In this work, the main principles of sequential equivalent approximation are considered, which allow for a notable sim-plification of the analysis by isolating stages where only one phenomenon is dominant. В роботі розглянуто перше наближення в оцінці початкового стану коріуму в нижній камері змішування під час пізньої стадії важкої аварії перспективного малого модульного реактора проекту ЕСС-SMART [1]. Особливості наведеного аналізу пов’язані як з початковим надкритичним станом теплоносія, так і з горизонтальною компоновкою активної зони у вигляді системи паралельних тепловиділяючих збірок із семирівневою системою заходу теплоносія [2]. Існуючі галузеві розрахункові системні інструменти є обмеженими в представлені оригінальної геометричної конфігурації проточної частини реактора, та зокрема активної зони. До того ж досі виникають суттєві складності із врахуванням декомпресії із надкритичного стану в двофазний, що суттєво обмежує виконання оцінок застосовуючи один аналітичний інструментарій. В даній роботі розглянуті основні принципи послідовного еквівалентного наближення, що дозволяє суттєво спростити аналіз за рахунок виокремлення стадій, в яких домінантним є лише один феномен.
Оцінка початкового стану басейну розплаву при деградації активної з горизонтальним розміщенням ТВЗ
Keywords: severe accident; supercritical parameters; core degradation; corium; horizontal fuel assembly; ECC-SMART; важка аварія; надкритичні параметри; деградація активної зони; коріум; горизонтальні ТВЗ; ECC-SMART